Analysis and Optimization of Supply Chain Operation Performance of Characteristic Agricultural Products in County Region under Rural Revitalization Strategy - Li, Hongyuan (International Journal of Global Economics and Management, 2024)
Under the background of China’s rural revitalization strategy, it is of great significance to analyze and optimize the supply chain operation of characteristic agricultural products in the county region to help agricultural products “go out of the village and enter the city”. According to the characteristics of county development, the SCOR model is improved, and the analysis framework of supply chain operation performance of characteristic agricultural products is constructed. Taking the characteristic agricultural products in LJ City, Zhanjiang as an example, the supply chain operation research and data collection are carried out, and the Cloud Model is used to evaluate and analyze the operation performance. It is found that there are some key problems in it, such as poor information sharing, low processing degree of agricultural products, poor matching between planning and demand, and high loss rate of product distribution. Some optimization suggestions are put forward, such as building an industrial information sharing platform, developing agricultural products processing industry, establishing small-scale associations for proprietary agricultural products and speeding up the construction of cold chain logistics, in order to provide reference for the optimization of supply chain operation of characteristic agricultural products and help the realization of rural revitalization strategy.